2001
DOI: 10.1016/s0168-583x(00)00611-x
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic deformation of colloidal particles under MeV ion irradiation

Abstract: Spherical silica colloids with a diameter of 1:0 lm, made by wet chemical synthesis, were irradiated with 2±16 MeV Au ions at¯uences ranging from 2 Â 10 14 to 11 Â 10 14 cm À2 . The irradiation induces an anisotropic plastic deformation turning the spherical colloids into ellipsoidal oblates. After 16 MeV Au irradiation to a¯uence of 11 Â 10 14 cm À2 a sizeaspect ratio of 4.7 is achieved. The size polydispersity ($3%) remains unaected by the irradiation. The transverse diameter increases with the electronic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…They are complementary to the results of the particle shaping effect observed in the high ion energy range, in which the pattern transformation occurs by the spherical particle deformation into ellipsoidal or hexagonal ones without 2D lattice symmetry breaking, as reported by Zolnai et al at E = 500 keV [4], T. van Dillen et al [1,5,6] and Snoeks et al at 4 MeV [7,8], J. C. Cheang-Wong et al at 8 MeV [9], and by Skupinski et al at 25 MeV [10] ion energy, respectively.…”
supporting
confidence: 80%
“…They are complementary to the results of the particle shaping effect observed in the high ion energy range, in which the pattern transformation occurs by the spherical particle deformation into ellipsoidal or hexagonal ones without 2D lattice symmetry breaking, as reported by Zolnai et al at E = 500 keV [4], T. van Dillen et al [1,5,6] and Snoeks et al at 4 MeV [7,8], J. C. Cheang-Wong et al at 8 MeV [9], and by Skupinski et al at 25 MeV [10] ion energy, respectively.…”
supporting
confidence: 80%
“…[1][2][3] One of the most striking examples of this effect is the deformation of single colloidal particles under megaelectron-volt ion irradiation. 4,5 Spherical silica colloids expand perpendicular to the ion beam and contract parallel to the ion beam changing their shape to oblate ellipsoidal. This ion beam deformation technique provides a unique method to tailor the shape of colloidal particles and aggregates.…”
mentioning
confidence: 99%
“…Thus the resulting strained track represents the mesoscopic defect responsible for the anisotropic deformation. Van Dillen et al have demonstrated that free standing silica particles expand perpendicular and contract parallel to the ion beam changing their shape from spherical to oblate ellipsoidal [39,40]. Several authors have shown that in case when thin metallic glass or amorphous film placed on the top of a crystalline substrate is irradiated with energetic ions under some angle, shear cannot be prevented by the substrate because of the traction-free surface so that the entire amorphous layer is sheared [41][42][43].…”
Section: Resultsmentioning
confidence: 99%